The Current Economic Crisis: Causes, Cures and Consequences - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2009)
The financial crisis has brought about an economic recession which is more severe and widespread than any decline in production in the past 50 years. In the USA and Europe the decline in production over the entire economy was, however, much less than during the Great Depression of the 1930s. Only in manufacturing has the decline in some quarters of 2008-09 been equally sharp. This time, however, the economic policy makers reacted differently. The high income levels at the start of the crisis and the social systems in place were able to cushion the fall. The roots of the crisis are not only to be found in the financial sector but also in macroeconomic imbalances, in regulation failures and insufficient policy coordination. Previous experience shows that the length of the crisis will vary between the financial markets, the housing sector, production and employment, and that recovery could be slow, bumpy and fragile. Different approaches of economic policy are being systematically compared and we already discuss how the crisis can actually be turned into an opportunity. One even dares to suggest that some of the elements of the European Model (long-term orientation, stakeholder model) could serve as an example to the world, even if the crisis management in Europe is not without fault, and despite the fact that in the USA and China economic policy is reacting more decisively. It is necessary to coordinate European policy more closely internally as well as with that of the USA and of the dynamic economies of neighbouring countries and Asia in order to avoid further crises, and to proactively tackle worldwide problems such as climate change, and raw materials and food shortages.
Keywords: 330; Konjunktur; Finanzkrise; Stabilisierungspolitik; Wirkungsanalyse; Welt